525 Young driver crashes – the influence of road sinuosity. (1st September 2016) - Jones, Sarah J; Lyons, Ronan A
Abstract : Background: Young drivers (YD) are at high risk of crashing because of their age and inexperience, leading some to 'test' themselves on roads that they perceive to be more challenging. While this may have applied more to male YD in the past, crash data indicate that whilst male YD crashes have decreased rapidly in recent years, female YD crashes have decreased much more slowly. Research suggests that female YD are beginning to show behaviours previously seen as 'male' and linked to crash risk. This paper aimed to examine the links between road crashes amongst male and female YD and older drivers (OD) and road sinuosity. Methods: Police road crash data on single vehicle crashes were analysed for Wales for 2000–2013. Young drivers were aged 17–19 years and older drivers aged 30–59 years. Each crash was linked to the road network segment (length of road between two consecutive junctions) on which it occurred. Sinuosity of the segment was the ratio of the actual segment length to the straight line distance between start and end of the segment. Analysis was by year, for males and females and for night-time v day time. Results: For 17–19 year male YD, 95 th percentile sinuosity values ranged from 1.14 to 1.24, with no trends. For females aged 17–19, 95 th percentile values ranged from 1.12 to 1.36 and showed a trend to increasing sinuosity of road crash segments. Amongst OD 95 th percentile sinuosity values were lower (1.11–1.28 for males, 1.12–1.31 for females) and decreased over time. Conclusions: YD crashes occur on more sinuous roads than OD crashes. This confirms previous findings around road type and relates specifically to the section of road on which the crash occurred. Realistically though, making the road network less sinuous is not a viable intervention; therefore addressing factors that place YD at higher risk on these roads is important. For YD, this means restricting alcohol consumption, passenger carriage and night-time driving, in short Graduated Driver Licensing.